Twibel: A matter of Internet privacy. Issue 2 (2nd April 2016) - Placid, Raymond; Wynekoop, Judy
ABSTRACT: Social media websites have become a powerful communication tool, where an individual can communicate with one person or millions of people at once. As a consequence, individuals are utilizing social media to report newsworthy events, as well as to post opinions, which may include posting negative information about another person or entity that can be harmful to such person's or entity's reputation (i.e., defamation), a phenomenon that is new to the legal system. This article reviews the legal precedent in the United States that addresses the legal impact of a defamatory statement sent through a social media website such as Twitter. Although the law in the United States is evolving, precedent indicates that the website's nature is generally less important than the nature of the communication. However, the law is not settled for cases in which a private tweet is released into the public domain unintentionally or by an accidental cause, such as a software defect.